Follicular microenvironment: Oxidative stress and adiponectin correlated with steroids hormones in women undergoing in vitro fertilization. Issue 2 (18th December 2020) - Luti, Simone; Fiaschi, Tania; Magherini, Francesca; Modesti, Pietro A.; Piomboni, Paola; Semplici, Bianca; Morgante, Giuseppe; Amoresano, Angela; Illiano, Anna; Pinto, Gabriella; Modesti, Alessandra; Gamberi, Tania
Abstract: Research has been focused on determining the follicular microenviroment produced by the theca and granulosa cells since the molecular characterisation of this body fluid could lead to the understanding of several fertility problems. Oxidative stress may be one of the factors involved in female infertility since it plays a key role in the modulation of oocyte maturation and finally pregnancy. An increase in oxidative stress is correlated with inflammation and intense research was developed to understand the interaction between inflammation and adiponectin, based on the fact that many adipokines are inflammation related proteins linked to reactive oxygen species production. The aim of this study is to investigate the correlation between total adiponectin levels and oxidative stress amount in the serum and follicular fluid (FF) of women who undergone in vitro fertilization. Moreover we verified the expression of adiponectin in granulosa and cumulus cells. To clarify the predictive value of steroid hormones in human assisted reproduction, twelve steroid hormones in FF and serum, were quantified in a single run liquid chromatography/mass spectrometry, by using a multiple reaction monitoring mode and we related the serum and follicular fluids adiponectin levels with the concentration of the investigated steroid hormones. Graphical abstract: oxidative stress is one of the factors involved in female infertility playing a key role in oocyte maturation. Adipokines are inflammation related proteins linked to reactive oxygen species production. There is a correlation between total adiponectin levels and oxidative stress amount in the serum and follicular fluid of women who undergone in vitro fertilization. There is a relation among the serum and follicular fluid adiponectin level with the concentration of several steroid hormones.